Solve this problem using substitution and then check it?:

y= -3x-2

2x+5y=16

y= -3x-2

2x+5y=16

You have to get a variable by itself like in here. Y is itself so in the other equation or we can say second one you just have to sub it in. Like

2x+5(-3x-2)=16

2x-15x-10=16

Now you just have to subtract 2 from 15, because of the same variable that is (x)

So -13x-10=16

Take 10 to the other side means add from the both sides, that will get you at

-13x=26

So now x= -2

Remember you added because it was -10 if it would be a positive 10 then you have to subtract it from both of the sides but since here it was negative so you just added them up

We have the variable y so lets substitute

y=-3x-2

2x+5y=16

2x+5y=16

2x+5(-3x-2)=16

2x-15x-10=16

-13x=26

x=-2

y=-3x-2

=-3(-2)-2

=4

2x+5y=16

2(-2)+5(4)=16

-4+20=16

16=16

RELATED: